Hematopoietic cell transplantation for all: report from the 2025 Congress of the Brazilian Bone Marrow Transplantation and Cellular Therapy Society - Duarte, Fernando Barroso; Melo, Andresa Lima; Arantes, Adriano; Bonfim, Carmem Maria Sales (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
This article provides an analysis of the current landscape of hematopoietic cell transplantation (HCT) in Brazil, highlighting current data, challenges, and ongoing initiatives, as presented at the Brazilian Society of Cellular Therapy and Bone Marrow Transplantation (SBTMO) 2025 meeting. Brazil has seen a significant increase in the number of HCT procedures in recent years, being the country with the highest number of transplants, HCT centers, and transplant teams in Latin America. However, important challenges remain, including regional disparities in access, limited local availability of HCT, and insufficient hospital beds. These topics were discussed alongside partial updates of the new National Transplant System (SNT) regulations with representatives from SBTMO, SNT, Brazilian Health Regulatory Agency, Brazilian National Cancer Institute, Brazilian Association of Lymphoma and Leukemia, and Brazilian Association of Hematology, Hemotherapy, and Cellular Therapy, to improve equity, safety, and outcomes of hematopoietic stem cell transplants across Brazil.